Execution quality: An analysis of fulfillment errors at a retail distribution center. Issue 1 (31st July 2015) - Craig, Nathan; DeHoratius, Nicole; Jiang, Yan; Klabjan, Diego
Abstract: Purchase orders specify many aspects of a fulfillment process, including item quantity, delivery time, carton labeling, bar coding, electronic data interchange, retail ticketing, and others. These fulfillment terms are instrumental for highly optimized retail supply chains employing automation and techniques such as pack‐by‐store. When fulfilling a purchase order, a supplier may commit a fulfillment error, i.e., the supplier may fail to adhere to the terms specified by the retailer. The retailer may then penalize the supplier for the fulfillment error via a chargeback deduction, which reduces the supplier's revenue. We present a study of the fulfillment errors and chargebacks that occur in practice using data collected from a major retailer's distribution center. While fulfillment errors involving incorrect product quantities and delivery times have received the most attention in the literature, we find that the majority of fulfillment errors in the context we study involve documentation, bar coding, and retail ticketing. We refer to these as correctable fulfillment errors, since they are amended at the retailer's distribution center through rework. We develop a model of inventory management with correctable fulfillment errors and use the retailer's data to assess the cost of these correctable fulfillment errors to the retailer's inventory system. Our research provides guidance to managers in identifying products and suppliers that impose large fulfillment error costs as well as in setting appropriate chargebacks for fulfillment errors.